-43u-52=32u-6

Combine u and 43.

-u⋅43-52=32u-6

Move 4 to the left of u.

-4u3-52=32u-6

-4u3-52=32u-6

Combine 32 and u.

-4u3-52=3u2-6

Subtract 3u2 from both sides of the equation.

-4u3-52-3u2=-6

To write -4u3 as a fraction with a common denominator, multiply by 22.

-4u3⋅22-3u2-52=-6

To write -3u2 as a fraction with a common denominator, multiply by 33.

-4u3⋅22-3u2⋅33-52=-6

Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.

Multiply 4u3 and 22.

-4u⋅23⋅2-3u2⋅33-52=-6

Multiply 3 by 2.

-4u⋅26-3u2⋅33-52=-6

Multiply 3u2 and 33.

-4u⋅26-3u⋅32⋅3-52=-6

Multiply 2 by 3.

-4u⋅26-3u⋅36-52=-6

-4u⋅26-3u⋅36-52=-6

Combine the numerators over the common denominator.

-4u⋅2-3u⋅36-52=-6

Simplify each term.

Simplify the numerator.

Factor u out of -4u⋅2-3u⋅3.

Factor u out of -4u⋅2.

u(-4⋅2)-3u⋅36-52=-6

Factor u out of -3u⋅3.

u(-4⋅2)+u(-3⋅3)6-52=-6

Factor u out of u(-4⋅2)+u(-3⋅3).

u(-4⋅2-3⋅3)6-52=-6

u(-4⋅2-3⋅3)6-52=-6

Multiply -4 by 2.

u(-8-3⋅3)6-52=-6

Multiply -3 by 3.

u(-8-9)6-52=-6

Subtract 9 from -8.

u⋅-176-52=-6

u⋅-176-52=-6

Move -17 to the left of u.

-17⋅u6-52=-6

Move the negative in front of the fraction.

-17u6-52=-6

-17u6-52=-6

-17u6-52=-6

Add 52 to both sides of the equation.

-17u6=-6+52

To write -6 as a fraction with a common denominator, multiply by 22.

-17u6=-6⋅22+52

Combine -6 and 22.

-17u6=-6⋅22+52

Combine the numerators over the common denominator.

-17u6=-6⋅2+52

Simplify the numerator.

Multiply -6 by 2.

-17u6=-12+52

Add -12 and 5.

-17u6=-72

-17u6=-72

Move the negative in front of the fraction.

-17u6=-72

-17u6=-72

Multiply both sides of the equation by -617.

-617⋅(-17u6)=-617⋅(-72)

Simplify -617⋅(-17u6).

Cancel the common factor of 6.

Move the leading negative in -617 into the numerator.

-617⋅(-17u6)=-617⋅(-72)

Move the leading negative in -17u6 into the numerator.

-617⋅-17u6=-617⋅(-72)

Factor 6 out of -6.

6(-1)17⋅-17u6=-617⋅(-72)

Cancel the common factor.

6⋅-117⋅-17u6=-617⋅(-72)

Rewrite the expression.

-117⋅(-17u)=-617⋅(-72)

-117⋅(-17u)=-617⋅(-72)

Cancel the common factor of 17.

Factor 17 out of -17u.

-117⋅(17(-u))=-617⋅(-72)

Cancel the common factor.

-117⋅(17(-u))=-617⋅(-72)

Rewrite the expression.

-1⋅(-u)=-617⋅(-72)

-1⋅(-u)=-617⋅(-72)

Multiply.

Multiply -1 by -1.

1⋅u=-617⋅(-72)

Multiply u by 1.

u=-617⋅(-72)

u=-617⋅(-72)

u=-617⋅(-72)

Simplify -617⋅(-72).

Cancel the common factor of 2.

Move the leading negative in -617 into the numerator.

u=-617⋅(-72)

Move the leading negative in -72 into the numerator.

u=-617⋅-72

Factor 2 out of -6.

u=2(-3)17⋅-72

Cancel the common factor.

u=2⋅-317⋅-72

Rewrite the expression.

u=-317⋅-7

u=-317⋅-7

Combine -317 and -7.

u=-3⋅-717

Multiply -3 by -7.

u=2117

u=2117

u=2117

The result can be shown in multiple forms.

Exact Form:

u=2117

Decimal Form:

u=1.23529411…

Mixed Number Form:

u=1417

Solve for u -4/3u-5/2=3/2u-6